2005
DOI: 10.1097/01.pgp.0000157918.36354.c1
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Human Papillomavirus Infection in Minimal Deviation Adenocarcinoma and Lobular Endocervical Glandular Hyperplasia

Abstract: The human papillomavirus (HPV) is basically always detected in squamous cell carcinoma of the cervix and its precursors; a high incidence of HPV also has been reported in adenocarcinoma and adenocarcinoma in situ of the uterine cervix. Lobular endocervical glandular hyperplasia (LEGH) was first described by Nucci in 1999. It is difficult to differentiate minimal deviation adenocarcinoma (MDA) from LEGH preoperatively or postoperatively by clinical and pathologic features. The relationships between HPV and MDA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 38 publications
1
34
0
1
Order By: Relevance
“…The STK11 gene has been identified as a tumor suppressor gene responsible for Peutz-Jeghers syndrome, and Kuragaki et al [19] have demonstrated that mutations in STK11 also have an important role in the etiology of MDA, as they may distinguish this rare tumor from more common types of AUC. HPV infection is not considered to be associated with MDA because high-risk HPV types (16 and 18) have been found in more than 80% of patients with mucinous adenocarcinomas of the cervix (MAC) but in no patients with lobular endocervical glandular hyperplasias (LEGHs) or MDA [22,23]. Kawauchi et al [23] discovered that a chromosomal gain or loss of genetic material was common in MDA (91%) and MAC (89%) lesions but occurred in only 21% of LEGH lesions.…”
Section: Discussion and Reviewmentioning
confidence: 99%
“…The STK11 gene has been identified as a tumor suppressor gene responsible for Peutz-Jeghers syndrome, and Kuragaki et al [19] have demonstrated that mutations in STK11 also have an important role in the etiology of MDA, as they may distinguish this rare tumor from more common types of AUC. HPV infection is not considered to be associated with MDA because high-risk HPV types (16 and 18) have been found in more than 80% of patients with mucinous adenocarcinomas of the cervix (MAC) but in no patients with lobular endocervical glandular hyperplasias (LEGHs) or MDA [22,23]. Kawauchi et al [23] discovered that a chromosomal gain or loss of genetic material was common in MDA (91%) and MAC (89%) lesions but occurred in only 21% of LEGH lesions.…”
Section: Discussion and Reviewmentioning
confidence: 99%
“…HPV sequence alignment and genotype-specific primer design was followed as previously reported by Nishiwaki et al 25 For PCR with HPV genotype-specific primers, 16 HPV genotypes (genotypes 6,11,16,18,30,31,33,35,39,45, 51, 52, 56, 58, 59, and 66) were detected by multiplex PCR in a single tube. PCRs were performed with a multiplex PCR kit (Qiagen Inc., Valencia, CA), following the manufacturer's instructions, with minor modifications.…”
Section: Hpv Dna Detection and Typingmentioning
confidence: 99%
“…19,20 Additionally, both neoplasms can be associated with lobular endocervical glandular hyperplasia (LEGH), 19 which represents a pyloric gland metaplasia 21 and has also been shown to be hr-HPV DNA-negative. 16,22 These facts suggest that the mucinous AC with gastric immunophenotype, incorporating MDA as its well-differentiated form in the morphological spectrum, is a distinct entity arising via a hr-HPV-independent pathway. In a previous investigation we demonstrated that mucinous AC with gastric immunophenotype was morphologically distinct with a good interobserver reproducibility, characterized by neoplastic cells with conspicuous cell borders and clear and/or pale eosinophilic voluminous cytoplasm, and aggressive clinical behavior.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hasta yüksek riskli olduğu düşünüldüğü için adjuvan KRT uygulanmıştır. MDA tanısı olan 25 vakanın bulunduğu bir yayında Human Papilloma Virus (HPV) pozitifliği araştırılmıştır (14). Vakaların dördünde (%16) HPV testi pozitif olarak bulunmuş, bunlardan birinde HPV tip 16, ikinci vakada tip 18 ve diğerinde ise tip16 ve 18 birlikte tespit edilmiştir.…”
Section: Uterin Serviksin Minimal Deviasyon Adenokarsinomu (Mda) -Gülunclassified